Publication and reporting of clinical trial results: cross sectional analysis across academic medical centers. (17th February 2016) - Chen, Ruijun; Desai, Nihar R; Ross, Joseph S; Zhang, Weiwei; Chau, Katherine H; Wayda, Brian; Murugiah, Karthik; Lu, Daniel Y; Mittal, Amit; Krumholz, Harlan M
Abstract : Objective To determine rates of publication and reporting of results within two years for all completed clinical trials registered in ClinicalTrials.gov across leading academic medical centers in the United States. Design Cross sectional analysis. Setting Academic medical centers in the United States. Participants Academic medical centers with 40 or more completed interventional trials registered on ClinicalTrials.gov. Methods Using the Aggregate Analysis of ClinicalTrials.gov database and manual review, we identified all interventional clinical trials registered on ClinicalTrials.gov with a primary completion date between October 2007 and September 2010 and with a lead investigator affiliated with an academic medical center. Main outcome measures The proportion of trials that disseminated results, defined as publication or reporting of results on ClinicalTrials.gov, overall and within 24 months of study completion. Results We identified 4347 interventional clinical trials across 51 academic medical centers. Among the trials, 1005 (23%) enrolled more than 100 patients, 1216 (28%) were double blind, and 2169 (50%) were phase II through IV. Overall, academic medical centers disseminated results for 2892 (66%) trials, with 1560 (35.9%) achieving this within 24 months of study completion. The proportion of clinical trials with results disseminated within 24 months of study completion ranged from 16.2% (6/37) to 55.3% (57/103) across academic medical centers. The proportion of clinical trials published within 24 months of study completion ranged from 10.8% (4/37) to 40.3% (31/77) across academic medical centers, whereas results reporting on ClinicalTrials.gov ranged from 1.6% (2/122) to 40.7% (72/177). Conclusions Despite the ethical mandate and expressed values and mission of academic institutions, there is poor performance and noticeable variation in the dissemination of clinical trial results across leading academic medical centers.